Reading in the early years handbook - Campbell, Robin (Buckingham ; Philadelphia : Open University Press, 1995)
This reference covers all aspects of children learning to read. It deals with a list of topics ranging from the "apprenticeship approach" to "nursery rhymes" to "whole language". The text also deals with organizational issues such as classroom management and time for literacy
Includes bibliographical references.
Keywords: Reading (Primary) -- Handbooks, manuals, etc